1970
DOI: 10.1136/bmj.2.5707.458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of the Effect of Vitamin B12 in Elderly Subjects with Low Serum B12 Levels

Abstract: Summary: A clinical trial of the effect of vitamin B12 therapy was conducted in 39 elderly subjects who had been found, in a community screening survey, to have low levels of serum B12 without a macrocytic anaemia or neuropathy. The study produced no evidence which suggests that in such subjects B12 is superior to placebo in effecting an improvement in psychiatric state or general well-being. There was a clear tendency for all the subjects to show an improvement during the trial, but this probably represents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…43 However, the course of subclinical deficiency often appears stationary. [61][62][63] The biochemical abnormalities themselves frequently fluctuate 64,65 ; mildly to moderately elevated MMA levels improved spontaneously in 44% of 432 cases retested 1 to 4 years later, and only 16% worsened. 64 Those observations notwithstanding, the impulse for medical intervention is such that controlled cobalamin trials in subclinical deficiency have been called unethical by some investigators.…”
Section: Expansion and Redefinition Of Cobalamin Deficiencymentioning
confidence: 99%
“…43 However, the course of subclinical deficiency often appears stationary. [61][62][63] The biochemical abnormalities themselves frequently fluctuate 64,65 ; mildly to moderately elevated MMA levels improved spontaneously in 44% of 432 cases retested 1 to 4 years later, and only 16% worsened. 64 Those observations notwithstanding, the impulse for medical intervention is such that controlled cobalamin trials in subclinical deficiency have been called unethical by some investigators.…”
Section: Expansion and Redefinition Of Cobalamin Deficiencymentioning
confidence: 99%
“…Hughes et al 23 also conducted a randomized trial of vitamin B 12 replacement in deficient subjects. They did not formally measure cognition but, based on a self‐report questionnaire and structured psychiatric interview, concluded that cobalamin was no better than placebo.…”
Section: Commentmentioning
confidence: 99%
“…As detailed in the following section, other investigators have handled this problem by conducting open-label studies (Martin et al ., 1992; Carmel et al ., 1995; Cunha et al ., 1995), sometimes with comparison to historical controls (Teunisse et al ., 1996; Eastley et al ., 2000) without low B 12 levels, and only rarely with full placebo-controlled designs (de la Fournière et al ., 1997; Hvas et al ., 2004). In elderly samples with no dementia, placebo-controlled trials of B 12 have sometimes handled the ethical dilemma by excluding subjects with any evidence of anemia or neurological symptoms (Hughes et al ., 1970; Seal et al ., 2002). However, this strategy is difficult to implement in practice, since minor hematological and neurological symptoms are prevalent in the elderly, and not necessarily related to low B 12 levels.…”
Section: Discussionmentioning
confidence: 99%